(untitled) (Lundiana: International Journal of Biodiversity, 2007)
The adult of Ambrysus (A.) attenuatus Montd. is redescribed. The larval instars V, IV, III and I are described and illustrated. Until now, there were only a few adults of the species in collections and its larvae were unknown. Some considerations are added about the habitat and the geographical localization of this species.